Ebleg Sebagai Alat Penataan Wayang Kulit dalam Kotak Penyimpanan - Sapto Sapto (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2022)
Wayang kulit has its own charm in the world of performing arts. The appointment of wayang as The World Master Piece of Oral and Intangible Heritage of Humanity from UNESCO on November 7, 2003, confirmed the existence of Wayang  in the community. Fifteen years later, on December 11, 2018, the President of the Republic of Indonesia, Joko Widodo, declared it as National Puppet Day. The attractiveness of wayang performances depends on the various supporting elements of the performing arts. These elements include the puppeteer, performance script, musical accompaniment, sound system and stage layout, etc. In addition, what is no less important is the governance or management of the puppets. Researchers, in this case, see that there are elements that play an important role in the procedures of storing and structuring these wayang; namely ebleg. Therefore, the author is interested in studying this ebleg further. The pattern of the arrangement of ebleg in the wayang storage box at Sanggar Mayangkara has a maximum of fourteen ebleg in one box. The ebleg is arranged in layers from bottom up by paying attention to the safety and durability of the puppets, the effectiveness and efficiency of the circulation of the puppets to support the puppeteer’s performances, as well as paying attention to the ergonomics side.